2013
DOI: 10.1111/1574-6941.12228
|View full text |Cite
|
Sign up to set email alerts
|

A gut microbiota-targeted dietary intervention for amelioration of chronic inflammation underlying metabolic syndrome

Abstract: Chronic inflammation induced by endotoxin from a dysbiotic gut microbiota contributes to the development of obesity-related metabolic disorders. Modification of gut microbiota by a diet to balance its composition becomes a promising strategy to help manage obesity. A dietary scheme based on whole grains, traditional Chinese medicinal foods, and prebiotics (WTP diet) was designed to meet human nutritional needs as well as balance the gut microbiota. Ninety-three of 123 central obese volunteers (BMI ≥ 28 kg m−2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
224
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(259 citation statements)
references
References 41 publications
20
224
1
4
Order By: Relevance
“…Those results suggest that modulation of the gut microbiota via dietary intervention could enhance the intestinal barrier integrity, reduce the circulating antigen load, and relieve the chronic inflammation that underlies metabolic syndrome. 25 That study is similar to our study in its use of a dietary intervention, fecal sample collection, and analysis of gut microbiota with pyrosequencing. However, Xiao et al 25 excluded participants with various pathologic conditions and used a stricter dietary intervention with three ready-to-use food formulas.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Those results suggest that modulation of the gut microbiota via dietary intervention could enhance the intestinal barrier integrity, reduce the circulating antigen load, and relieve the chronic inflammation that underlies metabolic syndrome. 25 That study is similar to our study in its use of a dietary intervention, fecal sample collection, and analysis of gut microbiota with pyrosequencing. However, Xiao et al 25 excluded participants with various pathologic conditions and used a stricter dietary intervention with three ready-to-use food formulas.…”
Section: Discussionsupporting
confidence: 58%
“…25 That study is similar to our study in its use of a dietary intervention, fecal sample collection, and analysis of gut microbiota with pyrosequencing. However, Xiao et al 25 excluded participants with various pathologic conditions and used a stricter dietary intervention with three ready-to-use food formulas. In addition, they examined the effects of their intervention using changes in the biomarkers along the pathway that likely connects gut microbiota to the pathogenesis of obesity, rather than focusing on subjective improvement in symptoms.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…26 Similarly, a 9-week intervention trial in 93 obese volunteers supplemented with a prebiotic showed concomitant changes in the intestinal microbiota and a reduction in intestinal permeability, assessed with a dual-sugar-absorption test. 27 Increased plasma concentrations of zonulin have also been reported in a cohort of 25 patients with sepsis compared with a healthy control group, stressing the potential role of tight junction proteins in sepsis, resulting in disruption of the structural integrity of the intestinal mucosa and increased intestinal permeability. 28 A high-fat diet dramatically increased intestinal permeability via a mechanism associated with reduced expression of epithelial tight junction proteins, including zonulin and occludin.…”
Section: Mucosa Permeabilitymentioning
confidence: 97%
“…Modification of the gut microbiota by a diet to balance its composition becomes a promising strategy to help manage obesity [18].…”
Section: Obesity and Metabolic Diseases And Their Link To The Intestimentioning
confidence: 99%